2014
DOI: 10.1007/s10616-014-9806-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of colorectal cancer stem-like cells

Abstract: This study is aimed at isolating colorectal cancer stem-like cells in vitro using a neurosphere assay method employed in isolating gliobastoma multiforme tumor cells. This was followed with confirmation of the isolated cells by flow cytometry, pluripotent genes expression and in vivo tumorigenicity assay. Using this culture assay, stem-like and non-stem-like CRC cells were isolated and expanded in vitro from purchased Balb/c mice induced with CT26 colorectal cancer (CRC) cell line. The procedure includes an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Expression of E-cadherin (Figure 3(a)), MUC2 (Figure 3(b)), vimentin (Figure 3(c)), and α -SMA (Figure 3(d)) was observed in these organoids. Since it was reported that expression of various stem cell markers was elevated in 3D culture compared with 2D culture [17], we next confirmed the existence of cancer stem cells in tumor ALI organoids (Figure 3(e)). Expression of a cancer stem cell marker, LGR5 in tumor organoids, was observed (Figure 3(e)).…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Expression of E-cadherin (Figure 3(a)), MUC2 (Figure 3(b)), vimentin (Figure 3(c)), and α -SMA (Figure 3(d)) was observed in these organoids. Since it was reported that expression of various stem cell markers was elevated in 3D culture compared with 2D culture [17], we next confirmed the existence of cancer stem cells in tumor ALI organoids (Figure 3(e)). Expression of a cancer stem cell marker, LGR5 in tumor organoids, was observed (Figure 3(e)).…”
Section: Resultssupporting
confidence: 62%
“…A recent report showed that 3D culture exhibits higher stemness and tumorigenicity than 2D culture [17]. It was also known that higher stemness leads to the resistance to anticancer drugs [18].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, analyses of short-term cultures (passages 2-7) showed stable expression of these different cell surface markers among the cultured CSC populations. The cell surface markers, CD26, CD29, CD44, CD54, CD49b, CD49f CD133, CD90 and CD326 (EpCam) have been reported to be present on human SC and CSC in various solid tumors [44-51]. CD24 and CD66 have been shown to identify mature/differentiated cells in normal and cancer tissues, including breast cancer [52, 53].…”
Section: Resultsmentioning
confidence: 99%
“…The second is dependent on the characteristic of specific enzymes, such as aldehyde dehydrogenase 1 (ALDH1) (23) and ATP-binding cassette subfamily G member 2 (ABCG2) (24). The third is culturing the cells in serum-free, low-adhesion conditions in vitro and enriching suspending colospheres (25). The methods for identifying CCSC properties include evaluating the ability of continuous sphere formation in vitro , continuous tumorigenicity in NOD/SCID mice and the similarity of differentiation between xenograft tumors and primary tumors.…”
Section: Introductionmentioning
confidence: 99%